Variation in physical and physiological seed quality caused by the origin of the H-520 corn hybrid - Andres-Meza, Pablo; Juárez-San-Juan, Jesús; Mejía-Contreras, José A.; Molina-Moreno, Juan C.; Sierra-Macías, Mauro (Revista Mexicana de Ciencias Agrícolas, 2025)
The physical and physiological quality of seeds are parameters that directly influence during establishment in the field, impacting the viability and vigor of seeds and seedling. The objective was to assess the variation in physical and physiological quality caused by the origin in seed production of the H-520 white-grained tropical corn hybrid. Seed samples were obtained from different seed companies. Physical and physiological variables were recorded in seeds and seedlings. The data analyzed showed differences (p≥ 0.05) in most of the physical and physiological variables of seeds, except for the variables of percentage of anthocyanins in seedling and plumule length. The mean values obtained for the standard germination test were (95.2%), normal plants (90.5%), abnormal plants (4.6%), non-germinated seeds (4.9%), presence of anthocyanins (50.35%), plumule dry weight (36.4 g), plumule length (11.5 cm), radicle length (15.3 cm), radicle dry weight (24.7 g), seed width (8.7 mm), seed length (11.5 mm), seed thickness (4.1 mm), weight of 1 000 seeds (238.7 g), flotation index (27.3), and hectoliter weight (76.6 kg hl-1). Although the tests carried out showed variations in the physical and physiological quality of seeds of the origins, the values are acceptable, suggesting that the management in seed production of the H-520 corn hybrid has been effective over time.
Keywords: Zea mays L.; commercial hybrid; seed-producing companies; seed test; varietal maintenance